The anxiety of being Australian: Modernity, consumerism, and identity politics in Michelle de Kretser's The Lost Dog. (June 2020) - Mirza, Maryam
Tom Loxley, the Anglo-Indian protagonist of Michelle de Kretser's 2007 novel The Lost Dog, has a difficult relationship with his adopted country Australia, one that is riven with anxiety as well as a profound sense of loss. This portrayal echoes, in many respects, the not uncommon representation in postcolonial fiction of the feelings of alienation and exclusion experienced by immigrants of colour in advanced capitalist countries. But in The Lost Dog, De Kretser's nuanced portrayal of Tom's tense ties with Australia and with other human beings also firmly situates immigrant experiences in the context of global capitalist modernity in general, and consumerism in particular. This article demonstrates that, without neglecting the implications of his racialized identity and without underestimating the trauma of physical displacement, De Kretser's depiction of Tom's identity crisis reveals the complex ways in which the notions of inclusion and exclusion, loss and belonging in contemporary Australia are inextricably tied in with the workings of global consumer capitalism.